Magnetic Chern bands and triplon Hall effect in an extended Shastry-Sutherland model - Malki, Maik; Schmidt, Kai Phillip (Physical Review B, 2017)
We study topological properties of one-triplon bands in an extended Shastry-Sutherland model relevant for the frustrated quantum magnet SrCu2(BO3)(2). To this end perturbative continuous unitary transformations are applied about the isolated dimer limit allowing us to calculate the one-triplon dispersion up to high order in various couplings including intra-and interdimer Dzyaloshinskii-Moriya interactions and a general uniform magnetic field. We determine the Berry curvature and the Chern number of the different one-triplon bands. We demonstrate the occurrence of Chern numbers +/- 1 and +/- 2 for the case that two components of the magnetic field are finite. Finally, we also calculate the triplon Hall effect arising at finite temperatures.